Secondary Agriculture: cognizance of faculty and students of University of Agricultural Sciences, Bangalore - Chaithrashree J; Y.N. Shivalingaiah; H.K. Pankaja (Utan Kayu Publishing, 2024)
Secondary Agriculture in recent days has alluring the concentration of all the stakeholders in Agriculture. Even though, word secondary agriculture looks familiar, the meaning of that word is vague. The present study was to analyse the awareness and attitude of Faculty and Students about secondary agriculture in university of Agricultural sciences, Bangalore during 2023-24. The structured questionaries’ was used to collect the primary data; ninety samples were considered for the study consisting of thirty faculty, thirty post graduate students and thirty undergraduate students. It was evident that more than half of the respondents possessed medium awareness (55.55 %) about secondary agriculture followed by low (28.88%) and high (15.55 %) awareness. But less number of respondents were had correct knowledge (20.00 %) regarding secondary agriculture. About 37.78 per cent of respondents belonged to high attitude category followed by medium (34.44 %) and low (27.78 %) attitude towards secondary agriculture. Attitude statement Secondary agriculture helps in employment generation across India ranked first with mean score of 4.23 and Rural industrialization helps in creating linkage between primary and secondary agriculture (Rank II = 4.12). The major constraints expressed in promoting secondary agriculture were Inconsistent supply of raw materials (Relative Importance Index = 0.853), Lack of farmer’s awareness regarding secondary agriculture and requires technical expertise (Relative Importance Index = 0.820). But according to findings of study, more than half of the respondents had awareness about secondary agriculture whereas only twenty per cent of the respondents possessed correct knowledge regarding secondary agriculture. In under graduation a course can be included for undergraduate students and HRD programmes can be acquainted to faculties of Agricultural sciences. In under graduation a course can be included for undergraduate students and HRD programmes can be acquainted to faculties of Agricultural sciences.